2014
DOI: 10.1128/aem.01837-14
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Acinetobacter baylyi ADP1 for Improved Growth on Gluconate and Glucose

Abstract: A high growth rate in bacterial cultures is usually achieved by optimizing growth conditions, but metabolism of the bacterium limits the maximal growth rate attainable on the carbon source used. This limitation can be circumvented by engineering the metabolism of the bacterium. Acinetobacter baylyi has become a model organism for studies of bacterial metabolism and metabolic engineering due to its wide substrate spectrum and easy-to-engineer genome. It produces naturally storage lipids, such as wax esters, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…More recently, an optimized alkane production pathway was integrated in the strain (Lehtinen, Virtanen, et al, ). Microbial wax esters and alkanes have previously been produced using carbon sources such as glucose and organic acids (Cao et al, ; Fatma et al, ; Kannisto, Aho, Karp, & Santala, ; Lehtinen, Efimova, et al, ; Lehtinen, Efimova, et al, ; Lehtinen, Santala, et al, ; Salmela, Lehtinen, Efimova, Santala, & Mangayil, ; Santala, Efimova, Karp, & Santala, ; Santala, Efimova, & Santala, ; Schirmer, Rude, Li, Popova, & del Cardayre, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, an optimized alkane production pathway was integrated in the strain (Lehtinen, Virtanen, et al, ). Microbial wax esters and alkanes have previously been produced using carbon sources such as glucose and organic acids (Cao et al, ; Fatma et al, ; Kannisto, Aho, Karp, & Santala, ; Lehtinen, Efimova, et al, ; Lehtinen, Efimova, et al, ; Lehtinen, Santala, et al, ; Salmela, Lehtinen, Efimova, Santala, & Mangayil, ; Santala, Efimova, Karp, & Santala, ; Santala, Efimova, & Santala, ; Schirmer, Rude, Li, Popova, & del Cardayre, ).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously demonstrated that a knock-out of the isocitrate lyase in Pseudomonas putida improved the production of PHAs when grown on gluconate, apparently for providing surplus acetyl-CoA for the PHA synthesis ( Klinke et al, 2000 ). Some bacteria also exhibit an alternative pathway for glycolysis, such as the modified Entner-Doudoroff pathway of certain Acinetobacter strains ( Young et al, 2005 , Kannisto et al, 2014 ). An interesting feature of the glycolysis of Acinetobacter is the oxidation of glucose to gluconate prior to the transport to cells.…”
Section: Introductionmentioning
confidence: 99%
“…A. baylyi ADP1 is a promising chassis for genetic studies, metabolic engineering, and lipid production [2630]. The strain naturally produces storage lipids, and thus the central metabolism is wired for the efficient production of fatty acyl-derived molecules.…”
Section: Introductionmentioning
confidence: 99%